Chromanone Acid Derivatives from the Stem Bark of Calophyllum incrassatum - U. Hasanah (IOP Publishing, 2019)
Abstract. Two chromanone acid derivatives, calofolic acid B (1) and apetalic acid (2) were isolated from the stem bark of Calophyllum incrassatum. The structures of both compounds were elucidated by UV, IR, HRESIMS, 1D and 2D NMR spectroscopies and comparison of their data with literatures. Compounds 1-2 were evaluated for their cytotoxic activity against P-388 cells, compound (1) showing value IC 50 1.14 μg/mL.